A Comparison of Training and Competition Demands in Semiprofessional Male Basketball Players. Issue 1 (2nd January 2018) - Fox, Jordan L.; Stanton, Robert; Scanlan, Aaron T.
ABSTRACT: Purpose : The purpose of this study was to quantify and compare training and competition demands in basketball.Methods : Fifteen semiprofessional male basketball players wore microsensors during physical conditioning training (PCT), games-based training (GBT), and competition to measure absolute and relative (·min −1 ) PlayerLoad TM (PL) and estimated equivalent distance (EED). Internal responses were calculated using absolute and relative session rating of perceived exertion (sRPE) and summated heart rate zones (SHRZ). Integrated measures were calculated as sRPE:PL and SHRZ:PL ratios.Results : PlayerLoad (arbitrary units [AU]) and EED (m) were statistically significantly ( p < .05) higher during PCT (632 ± 139 AU, d = 1.36; 5, 964 ± 1, 312 m, d = 1.36; 6.50 ± 0.81 AU·min −1, d = 2.44; 61.88 ± 7.22 m·min −1, d = 2.60) and GBT (624 ± 113 AU, d = 1.54; 5, 892 ± 1, 080 m, d = 1.53; 6.10 ± 0.77 AU·min −1, d = 2.14; 56.76 ± 6.49 m·min −1, d = 2.22) than they were during competition (449 ± 118 AU; 3, 722 ± 1474 m; 4.35 ± 1.09 AU·min −1 ; 41.01 ± 10.29 m·min −1 ). Summated heart rate zones were statistically significantly ( p < .05) higher during PCT (314 ± 86 AU, d = 1.05; 3.22 ± 0.50 AU·min −1, d = 1.94) and GBT (334 ± 79 AU, d = 1.38; 3.19 ± 0.54 AU·min −1, d = 1.83) than they were during competition (225 ± 77 AU; 2.17 ± 0.69 AU·min −1 ). The ratio of sRPE:PL was statistically significantly ( p < .05) higher during competition (1.58 ± 0.85) than during PCT (0.98 ± 0.22, d = 1.44) and GBT (0.91 ± 0.24, d = 1.90).Conclusion : Training demands exceeded competition demands.